IMPROVING ECONOMIC ANALYSIS IN CUSTOMS AUTHORITIES BASED ON INTERNATIONAL STANDARDS - Muydinova , Zilola (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
In the era of global trade integration, customs authorities serve as crucial institutions in managing trade flows, protecting fiscal revenues, and ensuring border security. However, economic analysis practices within customs systems often lack alignment with international standards, resulting in inefficiencies and data inconsistency. This study explores methods for improving customs economic analysis through the implementation of international frameworks such as those developed by the World Customs Organization (WCO), World Trade Organization (WTO), and International Monetary Fund (IMF). The research highlights methodological, institutional, and technological recommendations to enhance analytical capacity, transparency, and decision-making effectiveness.